DIAGNOSTICS OF HELICOBACTER PYLORI INFECTION BY ENZYME IMMUNOASSAY IN PATIENTS WITH CALCULOUS CHOLECYSTITIS - A. A. Yashnov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
In recentyears, the interest in the significance of Helicobacter pylori in various pathological processes is growing. The most studied is the role of Helicobacter pylori in gastroduodenal pathology. Gallstone disease is one of the most common diseases of the digestive system. Inflammatory changes in the biliary tract aggravate the clinical course of gallstone disease both in the preoperative and in the postoperative period and cause strictures, deformations of the extra hepatic bile ducts in the long term. One of the most threatening complications of gallstone disease is acute cholecystitis. Determination of IgG to Helicobacter pylori in complex diagnosis is important in patients with calculous cholecystitis. We conducted a prospective study of patients (n = 105) aged 30 to 50 years, suffering from different variants of calculous cholecystitis, in the preoperative and postoperative period by enzyme immunoassay. Enzyme-linked immunosorbent assay is reliable, affordable, least invasive method for diagnosing H. pylori infection. In patients with calculous cholecystitis, we marked a significant increase in IgG antibodies to Helicobacter pylori before surgical intervention and a subsequent reduction 10 days after it. Diagnosis of Helicobacter pylori infection of the gallbladder increases therapeutic efficiency and helps to develop preventive measures for complications of gallstone disease.